Complexity Effects in Information Systems on the Public Health Assistance Flows Integration - Souza, Marcílio Ferreira; Dornelas, Jairo Simião (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
The proliferation of information and communication technology and the advent of the Internet have resulted in a change in the level of complexity inherent in society and, consequently, in organizations, resulting in increasingly complex and integrated information systems. Complex information systems are understood as a special class of systems formed by a large number of heterogeneous subsystems, characterized by collective and emerging properties, which interact and influence each other through a diversity of connections and feedback loops. In this perspective, public health information systems, composed of several subsystems that need to interact, are characterized as complex. The research aimed to analyze, from the perspective of complexity theory, the effects of the integration of information systems in the assistance flows provided for SUS. 72 different health information systems were mapped, which formed a dense and interrelated network. The survey results revealed the following effects: self-organization tends to decrease the completeness and detail of the information circulating; coadaptation maximizes system coupling; fractality overloads information at the upper levels of the system; Emergency, on the other hand, helps to create innovative structures that integrate the complex system.